Penerapan Mesin Pengaduk Adonan Dan Etalase Produk Pada Usaha Pembuatan Kue Ulenan Dan Donat Di Pasar Tradisional Penfui Kota Kupang - Sahdan, Mustakim; Purnawan, Sigit; Muntasir, Muntasir; Rarindo, Hari; Awaluddin, Sri Prilmayanti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Community Partnership Program electric stirrer and storefront products for donuts, bread cakes and traditionalcakes have been implemented at business partners H. Harawiah and Toko Ujung in Kupang's Penfui market. Activitiesinclude the assembly of electric stirrers and cake display cases, training on the use and workings of tools, the process ofoperation and maintenance of electric stirrers and donut product storage window, assistance and reporting activities. Electric stirrer is a square steel plate, steel stirring rod, stirrer container, stirrer and electric dynamo. Stirrer specifications of dough capacity of 2-5 kg, dimensions of 60cm x 45cm x 53cm, stainless steel, 350 watts of power and 900-1200 rpm. The productstorage window is a 5mm aluminum and glass rod, dimensions of 100 cm x 40 cm x 100 cm. The method of implementation isthe provision of materials, the design and manufacturing of tools, demonstration of tools and the provision of tools by theteam, simulation of tools, counseling at partner locations and contributing to production resilience and mentoring activities.This community service output provides added value in terms of production, time and speed in mass production, and inhygienic and clean storage. Increase added value and selling value of donut cake products, fried bread cakes, traditional cakeswith a capacity of 2-5 kg driven by electricity, labor efficiency, increase partner productivity by producing 10-15 kg of breadper day or a mixture of 400 - 700 donuts, fried bread cake, traditional cake. Interviews with business partners receive a grossprofit of IDR 375,000.00 - 500,000.00 per day or 11,250,000.00 - 15,000,000.00 per month. Also partners put in a displaycabinet from this program